MATHEMATICAL MODEL OF COUNTERACTION TO THREATS IN PROTECTION SYSTEM OF CRITICAL INFORMATION RESOURCES - Галата, Лілія Павлівна; Корнієнко, Богдан Ярославович; Заболотний, Владислав Валерійович (Science-based technologies, 2019)
The article presents the main problems of information security of critical information resources and the reasons for their occurrence. Examples of the main threats to critical information resource protection systems found after the analysis of these incidents are considered. The analysis of the main approaches to the construction of mathematical models of information security systems is carried out. The mathematical model of counteraction to the influence of internal and external threats on the system of protection of critical informative resources of production of mineral fertilizers is proposed. The process of constructing a mathematical model for counteracting threats in the system of protection of critical information resources with the help of the Markov chain is gradually presented. The method of finding actual threats to data security during processing has been proposed. The program module has been developed by programming language Python. The research on the simulation model of the protection of critical information resources was conducted. Examples of calculations of the probability of finding a mathematical model of an information security system of critical information resources in one of the four states are presented (the threat did not occur, the threat came, but was not realized; the threat came, it was realized; the threat came, but was reflected by the system of protection). Examples of analyzing numerical results using the proposed methodology clearly show that their use helps to identify threats that are relevant to the system under study and can be used in practice. The disadvantage of the proposed method is the need to consider the behavior of the critical information resource protection systems under the influence of each type of threat separately and the impossibility of determining the behavior of the simultaneous action of several threats. But on the other hand, the study of the impact of each threat individually allows one to study in more detail each of its types and identify those whose likelihood of occurrence is greatest.